PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. PLN PERSERO AREA KLATEN - Yeni Sugena Putri (Faculty of Economics and Business Diponegoro University, 2016)
This study attempts to analyze 1) to know influence intellect intellectual on performanceemployees of PT. PLN Klaten area. 2) to know the influence of emotional intelligence onperformance employees of PT. PLN Klaten area. 3) to know the influence of the workplace onperformance employees of PT. PLN Klaten area. 4) to know influence intellect intellectual,emotional intelligence, and workplace simultaneously on performance employees of PT. PLNKlaten area.Methods used in research is cuantitative method, with the data collected based on the answerquesioner. In this casethe writer used Likert scale. Populations in this research are employeeof PT. PLN Klaten area amounting to 69 people, in this research called the populationresearch. Analysis techniques data in this research using multiple linear regression, t test , Ftest , the coeffiecient determination.The analysis shows that the: 1) due to tcount > ttable (3.230 > 1,996) with standard significant0,05 so Ho rejected and accepetd Ha, it means intellect intellectual have leverage toperformance employees of PT. PLN Klaten area. 2) due to tcount > ttable (4.167 > 1,996) itmeans Ho rejected and receive Ha means intelligence intelectual have leverage toperformance employees of PT. PLN Klaten area. 3) due to tcount > ttable (2.362 > 1,996),means Ho rejected and receive Ha means the workplace have leverage to performanceemployees of PT. PLN Klaten area. 4) the results of the hypothesis simultaneously in thisresearch, it can be locations that the fcount > f table (56,176 > 2,75 ) it means Ho rejected, itmeans intellect intellectual, emotional intelligence, and workplace simultaneously haveleverage to performance employees of PT. PLN Klaten area. 5) results linear regressionanalysis double Y = -5.636 + 0,397X1 + 0,501X2 + 0,353X3 value adjusted R square = 0,725shows that the contribution of all the variables independent is worth 72,5% the rest of 27.5 %influenced by other variables that is not described in this research.Keywords: Intellectual Intelligence, Emotional Intelligence, Environment of Work andPerformance